The Ando-Patagonian Stigmella magnispinella group (Lepidoptera, Nepticulidae) with description of new species from Ecuador, Peru and Argentina - Stonis, Jonas R.; Remeikis, Andrius; Diškus, Arūnas; Gerulaitis, Virginijus (Zootaxa, 2016)
On the basis of morphological studies of collection samples from the Andes (Ecuador, Peru and Argentina), we describe five new species of Stigmella Schrank (Lepidoptera: Nepticulidae): S. varispinella Diškus & Stonis, sp. nov. (Ecuador), S. olekarsholti Remeikis Diškus & Stonis, sp. nov., S. magnispinella Remeikis & Stonis, sp. nov. (Peru), S. dolia Remeikis & Stonis, sp. nov., and S. patagonica Remeikis & Stonis, sp. nov. (Argentina). All treated taxa belong to the newly designated S. magnispinella group. Images of adults and genitalia, pictorial keys, a distribution map, and photographs of the leaf-mines of S. olekarsholti are included.